Evidence of Potential Natural Products for the Management of Hypertrophic Scars - Thunyaluk Meetam PharmD; Apichai Angspatt MD; Pornanong Aramwit PhD (SAGE Publishing, 2024)
Hypertrophic scarring is an aberrant wound-healing response to reestablish dermal integrity after an injury and can cause significant abnormalities in physical, aesthetic, functional, and psychological symptoms, impacting the patient's quality of life. There is currently no gold standard for preventing and treating hypertrophic scars. Therefore, many researchers have attempted to search for antihypertrophic scar agents with greater efficacy and fewer side effects. Natural therapeutics are becoming attractive as potential alternative anti-scarring agents because of their high efficacy, safety, biocompatibility, low cost, and easy accessibility. This review demonstrates various kinds of natural product-based therapeutics, including onion, vitamin E, Gotu kola, green tea, resveratrol, emodin, curcumin, and others, in terms of their mechanisms of action, evidence of efficacy and safety, advantages, and disadvantages when used as anti-scarring agents. We reviewed the literature based on data from in vitro, in vivo, and clinical trials. A total of 23 clinical trials were identified in this review; most clinical trials were ranked as having uncertain results (level of evidence 2b; n = 16). Although these natural products showed beneficial effects in both in vitro and in vivo studies of potential anti-scarring agents, there was limited clinical evidence to support their efficacy due to the limited quality of the studies, with individual flaws including small sample sizes, poor randomization, and blinding, and short follow-up durations. More robust and well-designed clinical trials with large-scale and prolonged follow-up durations are required to clarify the benefits and risks of these agents.